2021
DOI: 10.21608/ejhc.2021.167095
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands, Job Resources and its Relationship with Job Crafting among Head Nurses

Abstract: Background: Organizations are continually under stress for existence in the present extremely changed work environment. During these times of continuously and emotionally demanding organizational changes, it is essential for associations to completely use and support nurses to become good crafters in their work to achieve organizational goals. Aim: The current study aims to investigate job demands, job resources and its relationship with job crafting among head nurses. Methods: A descriptive correlational rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…More than half of nurses reported that they used self-prescribed pharmaceutical medication and experienced signs and symptoms of episodic illness. These results are congruent with Lee et al (2017) (28) and Ahmed and Abd-ElGhani (2021) (29) who stated that job resources (job autonomy and performance feedback) and job demands (walk overload, emotional demands, technology demands) in the work context induced constant nurses job pressure. Attia et al (2021) (30) demonstrated a high level of job demand among nurses.…”
Section: Data Collection Techniquesupporting
confidence: 87%
“…More than half of nurses reported that they used self-prescribed pharmaceutical medication and experienced signs and symptoms of episodic illness. These results are congruent with Lee et al (2017) (28) and Ahmed and Abd-ElGhani (2021) (29) who stated that job resources (job autonomy and performance feedback) and job demands (walk overload, emotional demands, technology demands) in the work context induced constant nurses job pressure. Attia et al (2021) (30) demonstrated a high level of job demand among nurses.…”
Section: Data Collection Techniquesupporting
confidence: 87%